An Analysis of Digital Literacy Skills among Thai University Seniors - Piatip Phuapan; Chantana Viriyavejakul; Paitoon Pimdee (My University, 2016)
Digital literacy and the associated skills are becoming the basic and essential skill set of any employer that wishes to survive in a highly competitive world. Given the global importance of these skills for many sectors including education, medicine, information technology, tourism, etc., the researchers sought to determine which digital literacy skills were most important in using digital technology, communications tools, and/or networks to access, manage, integrate, evaluate, create and communicate information in order to function in a knowledge society. From a multistage random sampling survey of 400 second semester university seniors finishing their degrees in 2014 at 9 Thai public and private universities, it was determined that the ability to evaluate was the most important skill indicator in the development of digital literacy. Analysis was conducted by use of LISREL 8.72.
Keywords: LISREL; Digital Literacy; Digital era; Functional illiteracy; Technology-Enhanced Education Studies